Pengaruh Tingkat Kebisingan Terhadap Kemungkinan Resiko pada Daya Dengar Pekerja di Unit Rolling Mill 2 PT. Inti General Yaja Steel, Semarang - Adi Gadang Wiratmoko (Jurnal Teknik Lingkungan, 2012)
The growth of manufacturing industries in Indonesia, especially the rapidly growing steel industry, It also has the potential to cause noise both within the workplace and the environment because machines - used production. Noise can disturb workers which can harm the health impact on hearing loss if the exposure for a long time, it can also cause deafness. In this study discusses the effect of noise level on the possible risks of the power to hear the workers at Rolling Mill Unit 2 PT. Inti General Yaja Steel, Semarang. Noise levels in Rolling Mill 2 units ranged from 75-95 dBA measurements in each grid. Many grid areas still  exceed the noise standards based on the Decree of the Minister of Manpower No.KEP-51/MEN/1999. Audiometri tests were performed on 10 workers in the unit Rolling Mill 2 in PT Inti General Yaja Steel, shows that as many as 5 workers suffered minor deaf right ear and left ear, 1 person working experience being deaf in the right ear, 1 person working experience being deaf in the left ear, and 4 workers have the right and left ear conditions are still normal. Final Purpose of the study is expected to be minimized impact to reduced hearing of workers by monitoring and setting rules on sanctions (disciplinary action) for workers who do not keep the rules in the use of EPE (Ear Protective Equipment) is earplug.